2018
DOI: 10.3390/ijms19051272
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tumor Endothelial Cells in Cancer Progression

Abstract: Tumor progression depends on the process of angiogenesis, which is the formation of new blood vessels. These newly formed blood vessels supply oxygen and nutrients to the tumor, supporting its progression and providing a gateway for tumor metastasis. Tumor angiogenesis is regulated by the balance between angiogenic activators and inhibitors within the tumor microenvironment. Because the newly formed tumor blood vessels originate from preexisting normal vessels, tumor blood vessels, and tumor endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 77 publications
6
145
0
1
Order By: Relevance
“…109 Whether tumor angiogenesis is directly associated with increased metastatic risk is a subject of great debate, although it is generally accepted that tumor endothelial cells (TECs) contribute to critical steps of the metastatic cascade. 185,186 The association of angiogenesis with tumor metastasis seems to be due to interaction of TECs with TIE2 + TAMs accumulated after chemotherapy at perivascular sites, which increases TMEM assembly and function. 137 Although the current review focuses on chemotherapy, it should also be noted that a growing number of studies reported that TAMs limit the efficacy of anti-angiogenic therapies, mostly because TAMs shift the "angiogenic switch" toward the pro-angiogenic side.…”
Section: Chemotherapy-induced Angiogenesismentioning
confidence: 99%
“…109 Whether tumor angiogenesis is directly associated with increased metastatic risk is a subject of great debate, although it is generally accepted that tumor endothelial cells (TECs) contribute to critical steps of the metastatic cascade. 185,186 The association of angiogenesis with tumor metastasis seems to be due to interaction of TECs with TIE2 + TAMs accumulated after chemotherapy at perivascular sites, which increases TMEM assembly and function. 137 Although the current review focuses on chemotherapy, it should also be noted that a growing number of studies reported that TAMs limit the efficacy of anti-angiogenic therapies, mostly because TAMs shift the "angiogenic switch" toward the pro-angiogenic side.…”
Section: Chemotherapy-induced Angiogenesismentioning
confidence: 99%
“…angiogenesis, colorectal cancer, endothelial cells, integrin β1, sorting nexin 9 1 | INTRODUCTION One of the hallmarks in the development of solid tumors is tumor angiogenesis, the process of new blood vessel growth in tumor tissues from the pre-existing vasculatures (Folkman, 1971;Hida, Maishi, Annan, & Hida, 2018). The angiogenic activity of endothelial cells arises in response to various growth factors such as vascular endothelial growth factor (VEGF) and hepatocyte growth factor released from the neighboring tumor cells (Carmeliet & Jain, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the same tumor cells can secrete immunosuppressive factors, controlling the immune response [68][69][70] . Tumor-associated endothelial cells also contribute to make cancer physically inaccessible to the immune system by increasing deposition of factors that, on the one hand, confer a higher stiffness of the extracellular matrix and, on the other hand, prevent immune infiltration in the tumor tissue and favor tumor cell proliferation [69,71] . In light of these findings, several different immunotherapeutic strategies have been developed.…”
Section: Role Of Immunity In Resistancementioning
confidence: 99%